Spectrophotometric determination of platelet counts in platelet-rich plasma - Yutaka Kitamura; Masashi Suzuki; Tsuneyuki Tsukioka; Kazushige Isobe; Tetsuhiro Tsujino; Taisuke Watanabe; Takao Watanabe; Hajime Okudera; Koh Nakata; Takaaki Tanaka; Tomoyuki Kawase (SpringerOpen, 2018)
Abstract Background Platelet-rich plasma (PRP) is widely used in regenerative dentistry and other medical fields. However, its effectiveness has often been questioned. For better evaluation, the quality of individual PRP preparations should be assured prior to use. We proposed a spectrophotometric method for determination of platelet counts and validated its applicability using two types of PRP preparations. Methods Blood samples were obtained from healthy male volunteers and pure PRP (P-PRP) and leukocytes-rich PRP (L-PRP) were prepared using the double-spin method. In serial dilutions, platelet counts in P-PRP and L-PRP were determined using an automated hematology analyzer and a compact spectrophotometer. For validation, P-PRP and L-PRP independently prepared by three well-trained operators were used for comparison of the calculated and measured platelet counts. Results In the two types of PRP samples evaluated, platelet counts were almost equal and greater amount of both white blood cells (WBCs) and red blood cells (RBCs) were included in L-PRP preparations. The calibration curve obtained from serially diluted P-PRP showed a strong correlation (R 2 = 0.995), whereas that of L-PRP was relatively weaker (R 2 = 0.975). In validation testing, the scatter plot of the calculated platelet counts versus the measured values showed a strong correlation in P-PRP (R 2 = 0.671), whereas that of L-PRP showed a much weaker correlation (R 2 = 0.0605). Conclusions This method can precisely determine platelet counts in PRP preparations when the inclusion of WBCs or RBCs is minimized. Therefore, we recommend that clinicians use this method for quality assurance of individual PRP preparations.